Pengaruh Pengawasan terhadap Disiplin Kerja Pegawai Negeri Sipil pada Kantor Sekretariat DPRD Kota Probolinggo - Novi Sri Sandyawati (Journal on Education, 2021)
This study aims to determine the implementation of supervision regarding the level of discipline of Civil Servants and to find out how the influence of supervision on the discipline of civil servants at the secretariat office of the DPRD district of Probolinggo city. In this study the hypothesis put forward is "Supervision has a positive effect on discipline in the Probolinggo City DPRD Secretariat Office". The data were taken and obtained from 38 respondents who were carried out through the distribution of questionnaires/questionnaires, then processed through product moment correlation coefficient analysis and determinant coefficient analysis, which were then presented in the form of scientific analysis. Based on the results of the study, it was found that supervision had a positive influence on civil servant discipline and the effect was in the moderate category. This is evidenced by the results of the calculation of the product moment correlation coefficient, the results obtained are 0.425. then by calculating the correlation of the determinants obtained results of 18.06%. Which means that the increase in civil servant discipline by 18.06% is caused by the implementation of supervision, the rest is influenced by other variables not included in this study.